Melting relations of undersaturated alkaline Rocks. - Sood, M. K.; Edgar, A. D. (Meddelelser om Grønland, 1970)
As a continuation of a study reported by PIOTROWSKI and EDGAR (1970) on the melting and crystallization behaviour of undersaturated alkaline rocks from Greenland and elsewhere under different laboratory conditions, eight analysed rocks (5 from Greenland, 2 from Kenya and 1 from Tanzania) have been investigated at water vapour pressures up to 2070 bars; and two of the samples from the Ilímaussaq Intrusion, Greenland under conditions of controlled partial oxygen pressure at a total pressure of 1030 bars PH2O. The initial 1030 bar increment of PH2O decreases liquidus temperatures by 240-300° C compared to liquidus temperatures at one atmosphere pressure and for some samples alters the crystallization sequence. Lowering the PO2 decreases liquidus temperatures by as much as 30° C at 1030 bars PH2O and for the samples investigated an aegirine-rich clinopyroxene replaces feldspar as the primary phase at the liquidus. As in the previous study at one atmosphere pressure, rocks with a high agpaitic index have long melting intervals (300-460° C) at 1030 bars PH2O. The long melting intervals may be caused by the presence of higher proportions of volatiles, particularly Cl, F and H2O, in the agpaitic rocks compared to miaskitic rocks. In an alkaline melt these volatiles are present in the liquid rather than the gaseous phase. During crystallization the volatiles act more or less independently of one another and are " fixed" in the sodium-rich minerals sodalite, eudialyte, arfvedsonite and villiaumite. The initial excess of alkalies in comparison to aluminium in agpaitic melts enhances the probability of such a process. Results of experiments under different PO2 conditions suggest that in initially undersaturated magmas low Po2 conditions may favour a miaskitic differentiation trend whereas higher Po2 will favour an agpaitic differentiation trend. Melting and crystallization data obtained in the laboratory are generally in fair agreement with similar data obtained from field and petrographic observations.